Adaptive quantum genetic algorithm for task sequence planning of complex assembly systems. Issue 14 (1st July 2018) - Zhang, Linbin; Lv, Huanpei; Tan, Dapeng; Xu, Fang; Chen, Jiaoliao; Bao, Guanjun; Cai, Shibo
Abstract : Task sequence planning (TSP) is the key factor to the efficiency, stableness, and cost of a complex assembly system. To address the issue, an adaptive quantum genetic algorithm based on artificial potential field and gradient of object function is proposed to optimise the solving process, and to obtain the optimal TSP scheme. The simulation results indicate that the proposed algorithm can perform higher efficiency and stableness than the previously reported methods.